Micro $α g $-irresolute Maps in Micro Topological Spaces - Rangasamy Anandhi; Nataraj Balamani (Sahand Communications in Mathematical Analysis)
In this paper, we initiate a stronger form of Micro $α g$-continuous maps called Micro $α g$-irresolute maps and study some of their properties. Also, we introduce Micro $α g$-closed maps and obtain their properties. Further, we derive some composition of maps using newly defined maps. In addition to this, we develop a new class of homeomorphism called Micro $α g$-homeomorphism and Micro $α gc$-homeomorphism and discuss some of their properties.